Pharmacological Activities of Psoralidin: A Comprehensive Review of the Molecular Mechanisms of Action - Javad Sharifi-Rad; Senem Kamiloglu; Balakyz Yeskaliyeva; Ahmet Beyatli; Mary Angelia Alfred; Bahare Salehi; Daniela Calina; Anca Oana Docea; Muhammad Imran; Nanjangud Venaktesh Anil Kumar; Maria Eugenia Romero-Román; Alfred Maroyi; et al. (Frontiers Media S.A., 2020)
Analysis of the most relevant studies on the pharmacological properties and molecular mechanisms of psoralidin, a bioactive compound from the seeds of Cullen corylifolium (L.) Medik. confirmed its complex therapeutic potential. In the last years, the interest of the scientific community regarding psoralidin increased, especially after the discovery of its benefits in estrogen-related diseases and as a chemopreventive agent. Growing preclinical pieces of evidence indicate that psoralidin has anticancer, antiosteoporotic, anti-inflammatory, anti-vitiligo, antibacterial, antiviral, and antidepressant-like effects. Here, we provide a comprehensive and critical review of psoralidin on its bioavailability, pharmacological activities with focus on molecular mechanisms and cell signaling pathways. In this review, we conducted literature research on the PubMed database using the following keywords: "Psoralidin" or "therapeutic effects" or "biological activity" or "Cullen corylifolium" in order to identify relevant studies regarding PSO bioavailability and mechanisms of therapeutic effects in different diseases based on preclinical, experimental studies. In the light of psoralidin beneficial actions for human health, this paper gathers complete information on its pharmacotherapeutic effects and opens new natural therapeutic perspectives in chronic diseases.